Analysis of microcystins using high‐performance liquid chromatography and magnetic solid‐phase extraction with silica‐coated magnetite with cetylpyridinium chloride. Issue 8 (15th March 2017) - Li, Qiuying; Lian, Lili; Wang, Xiyue; Wang, Runnan; Tian, Yuanyuan; Guo, Xiaoyang; Lou, Dawei
Abstract : Microcystins (MCs), produced by freshwater cyanobacteria, can be serious water pollutants, so it is important to monitor their concentration in drinking water. We have developed a method for rapid and accurate determination of microcystin levels in environmental water, using magnetic solid‐phase extraction and high‐performance liquid chromatography with UV detection. The magnetic composite material, which was combined with cetylpyridinium chloride, was prepared by hydrothermal synthesis. The optimal extraction of microcystins in water sample was achieved by optimizing the amount of adsorbent, time of adsorption, ratio of eluting solvent, and volume of eluent. Under the optimal conditions, the limit of detection of MC‐LR was 0.001 μg/L, and the limit of quantification was 0.0028 μg/L. The limit of detection of MC‐RR was 0.001 μg/L, and the limit of quantification was 0.003 μg/L. These values are far lower than those established by the International Health Organization for the maximum concentration of microcystins in drinking water. The magnetic solid‐phase extraction adsorbent used in this method has the advantages of simple preparation, low price, and easy solid–liquid separation, and it can be used for the rapid and sensitive monitoring of trace microcystins in environmental water samples.